A Decade of Change and the Emergence of Digital Media: Analysis of Trade Press Coverage of the Advertising Industry, 2005–2014. Issue 1 (2nd January 2017) - McMillan, Sally J.; Childers, Courtney C.
ABSTRACT: This study uses Harold Innis's concepts of space- and time-biased media to examine digital media for 10 years beginning in 2005. Both syndicated spending data and industry trade press were used to assess trends and changes. After the recession of 2008, spending for online media surpassed spending on print for the first time. Digital was the dominant medium covered in most years of trade articles; however, the coverage of the rise (and fall) of media types was not as linear as was the actual change in spending. Additional analysis showed that trade press coverage focused mostly on the advertising agency business and that digital media were more central to core topics than were other media types. Concepts of time and space (Innis 1951, 2007) were also explored as overarching themes within the sample. Implications for theory, practice, and pedagogy are discussed.